2012
DOI: 10.1534/g3.112.003780
|View full text |Cite
|
Sign up to set email alerts
|

A TargetedIn VivoRNAi Screen Reveals Deubiquitinases as New Regulators of Notch Signaling

Abstract: Notch signaling is highly conserved in all metazoan animals and plays critical roles in cell fate specification, cell proliferation, apoptosis, and stem cell maintenance. Although core components of the Notch signaling cascade have been identified, many gaps in the understanding of the Notch signaling pathway remain to be filled. One form of posttranslational regulation, which is controlled by the ubiquitin-proteasome system, is known to modulate Notch signaling. The ubiquitination pathway is a highly coordina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 110 publications
2
34
0
Order By: Relevance
“…In an in vivo RNAi screen targeting Drosophila Ub-proteasome system (UPS) genes (Du et al, 2011;Zhang et al, 2012), we found that inhibiting Ubpy activity resulted in larval wing disc deformation and adult fly lethality, consistent with an essential role of Ubpy in the developing wing (Mukai et al, 2010). Correct patterning of adult wing relies on interplay among several signaling systems, including Hh, Notch (N) and Wingless (Wg) signaling.…”
Section: Resultsmentioning
confidence: 60%
See 2 more Smart Citations
“…In an in vivo RNAi screen targeting Drosophila Ub-proteasome system (UPS) genes (Du et al, 2011;Zhang et al, 2012), we found that inhibiting Ubpy activity resulted in larval wing disc deformation and adult fly lethality, consistent with an essential role of Ubpy in the developing wing (Mukai et al, 2010). Correct patterning of adult wing relies on interplay among several signaling systems, including Hh, Notch (N) and Wingless (Wg) signaling.…”
Section: Resultsmentioning
confidence: 60%
“…In contrast to the lack of effect of Ubpy on Hh signaling, reduced Wg signaling in Ubpy KO clones (supplementary material Fig. S4F; Mukai et al, 2010) and loss of margin bristles caused by Ubpy RNAi (Zhang et al, 2012) were observed. Developmental signaling proteins are trapped in enlarged endosomal vesicles…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…Deubiquitinases Notch [145] Cholesterol VEGF [146][147][148] MEF2 transcription factors VEGF-Notch [149] Podosomes VEGF-Notch [150] Adipogenic proteins VEGF-Notch [151,152] Glucose regulators VEGF-Notch [152,153] Foxo1 transcription factor EC metabolism [154] Lactate Angiogenesis [155] ROS and redox events VEGF [156][157][158] Cilia Angiogenesis [159,160] It has been shown that EC proliferative capacities can be stimulated by various inducers [41,42,164,165]. A variety of in vivo and in vitro models for understanding EC behaviour during angiogenesis at the cellular level have been derived from systems such as rabbit cornea [166], developing mouse retina [167], intersegmental vessel growth in zebrafish [168] and using ECs embedded in collagen or fibrin gels [169,170].…”
Section: Recently Identified For Sprouting Angiogenesis (Vegf/notch Pmentioning
confidence: 99%
“…org/). Of note, the USP encoding gene CG8232 was not included in this study [7,19]. The asterix (*) indicates the Usp genes not screened in [7].…”
Section: Additional Filesmentioning
confidence: 99%